2006
DOI: 10.5089/9781451863598.001
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Public-Private Partnerships in Infrastructure

Abstract: This Working Paper should not be reported as representing the views of the IMF.The views expressed in this Working Paper are those of the author(s) and do not necessarily represent those of the IMF or IMF policy. Working Papers describe research in progress by the author(s) and are published to elicit comments and to further debate. This paper presents an empirical analysis of the cross-country and cross-industry determinants of public-private partnership (PPP) arrangements. We find that PPPs tend to be more c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
3
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(35 citation statements)
references
References 15 publications
1
29
3
2
Order By: Relevance
“…Some studies have examined the key factors that influence PPP development from the macro-economic perspective [6]. Yehoue et al [16] found that countries with heavy debt burdens, a large market size, or a high institutional quality tend to encourage PPP development. Albalate et al [17] found that private sector is more willing to participate in PPP in the regions with higher possibility of recovering investment costs.…”
Section: Theoretical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have examined the key factors that influence PPP development from the macro-economic perspective [6]. Yehoue et al [16] found that countries with heavy debt burdens, a large market size, or a high institutional quality tend to encourage PPP development. Albalate et al [17] found that private sector is more willing to participate in PPP in the regions with higher possibility of recovering investment costs.…”
Section: Theoretical Analysismentioning
confidence: 99%
“…Firstly, infrastructure shortage refers to the gap between the aggregate demand and the stock supply of infrastructure. The aggregate demand for infrastructure was measured by per capita GDP (GDPPC) and the growth rate of annual per capita GDP (D_GDPPC) [16]. Per capita GDP reflects the level of economic development.…”
Section: Data and Variablesmentioning
confidence: 99%
“…The objective was for the provision of public capital assets and support services by a private sector consortium in exchange for a stream of (unitary) payments over the life of the contract. Overtime, it became the principal methods for procuring long-term public sector capital projects and delivering associated services in the face of the global financial crisis (HM Treasury, 1997;Broadbent & Laughlin, 2005;Grimsey & Lewis, 2005;Khadaroo, 2005 This support the findings of Hammami et al (2006) that PPPs tend to be more common in countries whose governments suffer from heavy debt burdens, where aggregate demand is sizable, and where markets are large enough to allow for cost recovery. They concluded that macroeconomic stability is essential for PPPs because partnerships are more common in countries with low inflation.…”
Section: Evolution Of the Public Private Partnershipmentioning
confidence: 72%
“…If a government is in financial difficulties, then the instrument of a PPP may offer a promising solution. The capital from private partners can make feasible infrastructure projects for which there is not enough public money available (Welch, 2006;Hammami et al, 2006). Moreover, consulting firms frequently report that PPP arrangements in many sectors can be expected to be more cost-efficient (i.e., cheaper) than conventional public procurement (see, e.g., PWC, 2005;Deloitte, 2006;Ernst & Young, 2007;KPMG, 2009).…”
mentioning
confidence: 99%